The QuadMax Task: Parametrically Manipulating Associative Memory Load across the Adult Lifespan. - Franco, Corinna Y.; Alcaraz-Torres, Alexander; Bennett, Ilana J. (Experimental Aging Research)
Adults of all ages are worse at recognizing pairs of items that were previously seen together relative to the individual items, and this paired-associative memory deficit is exacerbated in aging. Less is known about memory for higher associative loads, which place greater demands on binding processes that link items into a cohesive memory trace, among other processes (e.g., working memory, recollection). In this study, adults across the lifespan (n = 250, 18–78 years) completed a novel recognition task in which they studied word pairs, triplets, and quadruplets and were tested on their memory for repeated, recombined, and novel word sets. Associative memory deficits were seen in adults of all ages as fewer correct responses to repeated sets (hits), more incorrect responses to recombined sets (recombined false alarm, FA), and larger differences between these measures (associative memory) at higher set sizes. In addition, older adults had worse associative memory performance (higher recombined FA, lower associative memory) that increased at higher set sizes. These findings indicate that associative memory deficits increase with demands on binding or other processes at higher associative loads and with aging. They further demonstrate the feasibility of manipulating and assessing associative memory load using our novel QuadMax task.